Towards the integration of mindfulness and emotional intelligence in psychology and education - Moscoso, Manolete S. (2019)
Background: This article presents an empirical review of the integration of mindfulness and emotional intelligence. Mindfulness is a cognitive intervention model that helps people to develop awareness of their experience in the present moment favoring emotional self-regulation. Similarly, emotional intelligence has been conceptualized as a constellation of abilities related to the perception, understanding and adequate management of emotions within and among people. Both conceptual models are associated with a good sense of well-being and personal development. State of the art: This paper reviews the preliminary scientific evidence published in psychology and education literature, and examines the mediating effects of these two constructs in the process of emotional regulation and quality of life of individuals. Conclusions: The study results indicate that the interaction of mindfulness and emotional intelligence offers important benefits for people’s well- being. It was also reported that emotional intelligence acts as mediator between mindfulness and greater positive emotions. The purpose of this review article is to identify a model of integration for emotional regulation that includes «active ingredients» to influence well-being and the way in which the practice of mindfulness contributes to increase the abilities of emotional intelligence.